A Visual Analysis of Research Hotspots and Trends in Zhuangzi’s Thought from 2020 to 2025 - Xuelan Xiao; Ren, Huichan (Advances in Humanities and Contemporary Studies, 2025)
This study analyzes the research hotspots and trends in Zhuangzi’s thought from 2020 to 2025 by employing bibliometric analysis and visualization techniques. The findings reveal a steady decline in the number of publications. The field of philosophy has the highest document count. Scholars Chen Yun and Sun Mingjun have made significant contributions. However, their collaborative network is rather loose. The journal History of Chinese Philosophy has significantly contributed to the field. Current research hotspots include core concepts such as Xiaoyao You, Ziran, and Ziyou, alongside emerging themes like Xuanxue and Pre-Qin Daoism. This study offers a clear and comprehensive overview of the knowledge structure and evolving trends in the research of Zhuangzi’s thought through visualization analysis. It offers valuable insights for optimizing research directions, integrating academic resources, and fostering greater academic collaboration. Moreover, this research supports the creative transformation and innovative development of China’s rich traditional culture.